The ddifferent philosophies of higher education - Osman, Sharifuzah; Md Taib, Fauziah; Abdul Khalid, Siti Nabiha (2020)
Blackmore, Brennan, and Zipin (2010) and Rytmeister and Marshall (2007) claimed that many academic studies had been conducted to understand the philosophies of higher education or the purpose, the aims, or missions of higher education. A closer investigation found that most of the discussions mostly centered on the academic and market philosophies of higher education, while disregards the other philosophies of higher education. This include, the public, religion and cultural philosophy of higher education. Given that, the discussion on higher education philosophy often led to the tendency to treat HEIs as similar entities without recognizing their differences and plurality. Recognizing the different philosophies of higher education is crucial since different governance mechanism is needed to provide flexibility to the institution to fulfill diverse demand for higher education. Otherwise, sub optimal outcomes may be experienced by the HEIs, the state, and the whole society. To enrich the discussion on the higher education philosophy, this paper discusses the different philosophies of higher education found around the globe.